Impact of lifestyle‐related disease on conversion and reversion in patients with mild cognitive impairment: after 12 months of follow‐up. (22nd November 2015) - Osone, Akira; Arai, Reiko; Hakamada, Rina; Shimoda, Kazutaka
Abstract : Objective: The objective of the study is to investigate whether the lifestyle‐related disease (LSRD) hypertension, type II diabetes mellitus, and lipid abnormality are associated with conversion and reversion in patients with mild cognitive impairment (MCI) over 12 months of follow‐up. Methods: One hundred and thirteen patients with MCI were prospectively enrolled and longitudinally assessed. Methods used include mini‐mental state examination, the Japanese version of the cognitive subscale of the Alzheimer's Disease Assessment Scale, the Clinical Dementia Rating, the Frontal Assessment Battery, the Neuropsychiatric Inventory, magnetic resonance imaging, and quantitative single‐photon emission computed tomography. In addition, laboratory examinations of glucose and lipids were also performed. All measurements were performed at first intake and again at the end of the 12‐month follow‐up. Conversion was identified as a change in Clinical Dementia Rating from 0.5 to 1 and reversion as a change from 0.5 to 0. Results: Patients with MCI with reversion had lower comorbid lipid abnormality at baseline and higher cognitive and behaviour function across the 12‐month follow‐up compared with those with no change or conversion. Patients without comorbid LSRD had lower systolic pressure and lower glucose and triglyceride levels at baseline, as well as less cognitive decline compared with other groups across the follow‐up period. Conclusions: The absence of lipid abnormality at baseline may contribute to reversion in patients with MCI. The presence of multiple LSRD was associated with cognitive decline. Our results highlight the contribution of multiple LSRD on increasing conversion and decreasing reversion in patients with MCI. Copyright © 2015 John Wiley & Sons, Ltd.